Peningkatan Keterampilan Desain Grafis Berbasis Canva Untuk Mendukung Kreativitas SMK Trisakti di Era Digital - Nurhayati Sitorus; Jose Paskah Situmorang; Hetika Melda Yanti Panjaitan; Sri Renata Sagala (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2025)
Today's in digital era, graphic design skills have become one of the essential competencies, especially for students of Vocational High Schools (SMK) who are prepared to enter the workforce. However, challenges such as limited access to professional design software and a lack of adequate training often hinder students' creative development. Therefore, this training program is designed to enhance the graphic design skills of students at SMK Tri Sakti Lubuk Pakam by utilizing Canva. Canva was chosen as the main platform due to its ease of use, availability of various creative features, and accessibility in both free and paid versions. This program implements various methods, including theoretical and practical training, interactive workshops, and evaluation of students' design results. The activities will be conducted in stages, starting with an introduction to basic graphic design, exploring Canva features, and then applying them in creating various design works such as posters, promotional materials, and digital content. It is expected that through this training, students will improve their graphic design skills, making them more prepared to face the creative industry or develop their own business. Additionally, this program also aims to enhance the competitiveness of SMK Tri Sakti Lubuk Pakam graduates in the workforce and foster an innovative and creative culture among students.